2017
DOI: 10.3390/su9081477
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Energy Design Strategies for Retrofitting Mass Housing Estates in Northern Cyprus

Abstract: This research project is undertaken in the Turkish Republic of Northern Cyprus (T.R.N.C.). The objective of the research is to investigate the occupants' behaviour and role in the refurbishment activity by exploring how and why occupants decide to change building systems and how to understand why and how occupants consider using energy-efficient measurements. The housing estates are chosen from 16 different projects in four different regions of the T.R.N.C. that include urban and suburban areas. The study is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 17 publications
(16 reference statements)
0
14
0
Order By: Relevance
“…Dempsey and Burton (2012, p.18) emphasise the need for knowledge transfer among and between all stakeholders to raise the profile of 'place-keeping and the need for stakeholders to have both a strategic and local focus on long-term quality and efficiency'. It is also suggested that involvement of all stakeholders at all stages of the decision-making process that occur in regeneration and renewal contexts (Le Feuvre et al, 2016), and housing estate developments (Ozarisoy, 2018;Ozarisoy and Altan, 2017) is important. However, it is clear from reviewing the literature that the institutional dimension of participation and stakeholdership, and particularly the potential knowledge-building role of stakeholders in participatory processes is often poorly recognised or evaluated in terms of the process and the outcome/impact in participatory urban redevelopment projects.…”
Section: Participation and Urban Redevelopmentmentioning
confidence: 99%
“…Dempsey and Burton (2012, p.18) emphasise the need for knowledge transfer among and between all stakeholders to raise the profile of 'place-keeping and the need for stakeholders to have both a strategic and local focus on long-term quality and efficiency'. It is also suggested that involvement of all stakeholders at all stages of the decision-making process that occur in regeneration and renewal contexts (Le Feuvre et al, 2016), and housing estate developments (Ozarisoy, 2018;Ozarisoy and Altan, 2017) is important. However, it is clear from reviewing the literature that the institutional dimension of participation and stakeholdership, and particularly the potential knowledge-building role of stakeholders in participatory processes is often poorly recognised or evaluated in terms of the process and the outcome/impact in participatory urban redevelopment projects.…”
Section: Participation and Urban Redevelopmentmentioning
confidence: 99%
“…In reference [36], the authors studied what encourages people to increase their home's efficiency, and how they attempt to do it. Most popular approaches are focused on home renovations to decrease energy costs, however, people don't know how much energy it is possible to save by reducing the defined A/C temperature difference, compared to the outdoor temperature, or the potential a building and energy management system has to increase savings and automate some actions.…”
Section: Implementation At a Schoolmentioning
confidence: 99%
“…A number of methods is used in studies on energy efficiency and decrease in pollution, from qualitative [16] to quantitative ones. This paper takes a quantitative route.…”
Section: Methodsmentioning
confidence: 99%